Bridging Technology and Education: How Immersion and ‎Usefulness Drive Mobile AR Use in Medical and Health Science ‎Education - J, Paul Arun Kumar; K, Subathra (International Journal of Accounting and Economics Studies, 2025)
Using the Mobile Augmented Reality Acceptance Model, this study examines the motivations of current health science and medical ‎educators to incorporate MAR in their teaching methods. The MARAM augments the Technology Acceptance Model (TAM) by offering ‎proportional benefits, enjoyment, and ease of use, mobile self-efficacy, information seeking, flow, and novelty. Additionally, this study ‎examines MARAM validity. This study aimed to evaluate how well students learnt when the same material was presented in an augmented ‎reality environment. Professors from medical institutes received 370 questionnaires; 325 of them were determined to include information ‎that was appropriate for the study. Structural equation modeling with partial least squares is used to test the relationships among variables. Consumers are much more likely to use mobile augmented reality if they think it will save them time, be convenient, be fun, and ‎give them confidence. Additionally, empirical findings indicate that flow and information-seeking tendencies have a significant impact on ‎usage intention, whereas the role of novelty is comparatively minimal. These findings further emphasize the roles of immersion and perceived usefulness as mediators of the favorable outcomes from AR purchasing.
Keywords: Augmented Reality; MARAM; Technology Acceptance; Perceived Usefulness; Immersion; Intention to Use